Association between urinary levels of 8-hydroxy-2-deoxyguanosine and F2a-isoprostane in male football players and healthy non-athlete controls with dietary inflammatory and antioxidant indices - Zare, Mahsa; Shateri, Zainab; Nouri, Mehran; Sarbakhsh, Parvin; Eftekhari, Mohammad Hasan; Pourghassem Gargari, Bahram (Frontiers in Nutrition, 2023)
Purpose: Since the oxidative status in athletes is a pressing issue, and the links between anti-inflammatory and antioxidant potential of diet with oxidative biomarkers in athletes warrant further investigation, this study designed to assess oxidative-generated modifications of DNA and lipid using urinary 8-hydroxy-2-deoxyguanosine (8-OHdG) and F2alpha-isoprostane (F2a-IP), as well as the association between dietary inflammatory index (DII), dietary total antioxidant capacity (DTAC) and dietary phytochemical index (PI) with 8-OHdG and F2a-IP in male football players and their healthy non-athlete controls. Methods: In this descriptive-analytical study, 45 male football players and 45 healthy non-athletes, whom were individually matched based on age and BMI, were recruited from Shiraz City, Iran. Fasted urine samples were analyzed for 8-OHdG and F2a-IP levels. Anthropometric measurements were performed, and body composition was assessed using body composition analyzer. A valid food frequency questionnaire was recorded to calculate DII, DTAC and PI scores. For all data analysis, a suit generalized estimating equation (GEE) model was applied. Results: 8-OHdG (β=-6.96), F2a-IP (β= -82.58) and DII (β=-2.06) were significantly lower, while DTAC (β=2.37) and PI (β=0.084) were significantly higher in football player group compared with non-athlete group (P<0.001 for all variables). In all participants, dietary indices were statically significantly linked to oxidative biomarkers. DII was positively associated with 8-OHdG (β=2.25; P<0.001) and F2a-IP (β=38.34; P<0.001). Furthermore, negative associations between DTAC (β=-1.42; P< 0.001) and PI (β=-35.37; P< 0.001) with 8-OHdG were found. Also DTAC (β=-17.34; P< 0.001) and PI (β=-428.11; P=0.003) were negatively associated with F2a-IP. Conclusion: Our results highlighted the importance of healthy diet on oxidative status in football athletes. Urinary biomarkers of DNA and lipid oxidation were lower in football players compared to non-athletes, and it is likely that adherence to an anti-inflammatory and antioxidant-rich diet may lead to reduced oxidative stress.